2022
DOI: 10.1177/17470218221082657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of swearing on strength: Disinhibition as a potential mediator

Abstract: Introduction: Swearing fulfils positive functions including benefitting pain relief and physical strength. Here we present two experiments assessing a possible psychological mechanism, increased state disinhibition, for the effect of swearing on physical strength. Method: Two repeated measures experiments were carried out with sample sizes N=56, and N=118. Both included measures of physical performance assessing, respectively, grip and arm strength, and both included the Balloon Analogue Risk Task (BART) to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Despite the lack of evidence for autonomic activation, there was a consistent pattern of results demonstrating that swearing increased strength and power/performance relative to not swearing. A more recent set of experiments by Stephens et al (2022) also found that repeating a swear word increased participants' physical strength, measured in grip and arm strength. The fact that this outcome has been found consistently across the studies suggests that it is a reliable effect.…”
Section: Pain Relief Stamina and Strengthmentioning
confidence: 89%
“…Despite the lack of evidence for autonomic activation, there was a consistent pattern of results demonstrating that swearing increased strength and power/performance relative to not swearing. A more recent set of experiments by Stephens et al (2022) also found that repeating a swear word increased participants' physical strength, measured in grip and arm strength. The fact that this outcome has been found consistently across the studies suggests that it is a reliable effect.…”
Section: Pain Relief Stamina and Strengthmentioning
confidence: 89%
“…Another possibility is that the hypoalgesic effects of a taboo act are due to changes in self-regulation or state disinhibition. Stephens et al (2022) showed that producing a swear word increased self-confidence and distraction compared to producing a neutral word, suggesting that when people swear, they may feel more confident in their own abilities and may be better able to ignore aversive stimulation. This could then lead to higher pain tolerance on the cold pressor task, as participants feel more confident in their ability to persevere and are also better able to ignore the pain they are experiencing.…”
Section: Discussionmentioning
confidence: 99%
“…The positive physiological, psychological, and social effects of swearing may contribute to its high prevalence. Swearing has been shown to improve physical performance (Stephens et al, 2018(Stephens et al, , 2022Jiannine and Antonio, 2023), increase self-confidence (Stephens et al, 2022), increase humor (Beers Fägersten, 2012;Stephens et al, 2022), improve credibility (Rassin and van der Hay et al 10.3389/fpsyg.2024.1416041 Frontiers in Psychology 02 frontiersin.org Heijden, 2005), strengthen social connections (Daly et al, 2004;Stapleton, 2010;Beers Fägersten, 2012;Giffin, 2016), and improve memory and recall (MacKay et al, 2004;Jay et al, 2008). Thus, swearing appears to produce beneficial effects across various physiological and psychological domains.…”
Section: Introductionmentioning
confidence: 99%